Highly efficient Ho: YAP laser with 202 W of linearly polarized output power at 2118 nm - Ren, Chuanyong; Ma, Ke; Wang, Fei; Shen, Deyuan; Zhu, Heyuan (Frontiers in Physics, 2023)
We report on high power and efficient operation of a compact Ho: YAP laser in-band pumped at 1931 and 1943 nm with a high-power and narrow-linewidth Tm-doped fiber laser. Using a 0.5at. % Ho3+ doped Ho: YAP cut along the b-axis and a simple two-mirror resonator, up to 202 W of output power has been generated at ∼2118 nm for 336 W of absorbed pump power at 1931 nm, corresponding to a slope efficiency of 61.2% with respect to the absorbed pump power. The laser output is linearly polarized along the c-axis with a polarization extinction ratio (PER) of ∼20.0 dB. Results presented in this work verify the superior power scaling capability of Ho: YAP at ∼2.1 μm with high lasing efficiency.